Total Hip Arthroplasty the best Intervention for Femur-neck fractures - Priya Pralhad Desai; Suresh Kishanrao (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2021)
Fracture neck of femur is a common event in elderly people in India. Total Hip Arthroplasty (THA) has established as the better choice of surgical intervention. There are two major surgical approaches for performing a total hip replacement 1) the posterior approach 2) the anterior approach. The posterior approach to total hip replacement is the most used method and allows the surgeon excellent visibility of the joint, more precise placement of implants and is minimally invasive. In India, cemented modular hemiarthroplasty is being promoted using a cost-effective Indian implant that has confirmed distinct advantage. While the common cause of Femur neck fractures are falls in bathrooms or slipper floors. We are reporting a case of Femur neck fracture, after alighting from a bus. Due to the inaccessibility of THA in rural India, patient had to be shifted to the state Hqs. The course of surgery, hospital stay and outcome of Left side Total Hip Replacement (THR) therapy in an elderly male with known comorbidities is being narrated.  The patient had the shortest hospital stay of 5 days, was stable throughout the surgery, postoperative period, despite being diabetic and hypertensive and was back doing his normal activities within 6 months.